Cerebral small vessel disease does not impair leptomeningeal collateral supply in large-vessel occlusion: results from quantitative collateral mapping with MRI - Polkowski, Christoph; Helwig, Niklas; Seker, Fatih; Möhlenbruch, Markus Alfred; Wagner, Marlies; Seiler, Alexander (Journal of cerebral blood flow & metabolism, 2025)
We hypothesized that cerebral small vessel disease (CSVD) burden might not relevantly affect leptomeningeal collateral supply in patients with acute ischemic stroke (AIS) due to large-vessel occlusion (LVO). In n = 154 patients with anterior circulation LVO, CSVD imaging markers (white matter hyperintensities [WMH], lacunes, cerebral microbleeds and enlarged perivascular spaces) were assessed with MRI, using established criteria. Besides the extent of WMH, assessed using total Fazekas sum score, overall CSVD burden was determined with a total CSVD summary score ranging from 0-4. A quantitative and rater-independent collateral vessel index was computed from automated processing of T2*-weighted time series in perfusion-weighted imaging (PWI) to assess the pial collateral status. The overall burden of WMH and CSVD were not significantly associated with poor collaterals (adjusted odds ratios 0.830 (0.328-2.104) and 0.995 (0.666-1.488), p = 0.695 and p = 0.982) and did not modify the significant relationship of leptomeningeal collaterals with clinical stroke severity, ischemic core volume and infarct growth rate. Quantitative and objective analysis of collaterals with a signal variance-based approach in PWI revealed no overt association between CSVD burden and collaterals in LVO patients. Factors favoring or impairing collateral supply in case of acute cerebral ischemia warrant further exploration in future studies.